Screening of COPD patients using the COPD diagnostic questionnaire and a portable spirometer in primary healthcare institutions: a cross-sectional, diagnostic study - Feng Chen; Qingrong Nie; Xuefeng Han; Chunjuan Li; Qimeng Liu; Feifei Xu; Li Zhang; Le Qiao; Maoxin Li; Ying Zhang; Haiyan Wang (BMC Pulmonary Medicine)
Abstract Background Portable spirometers and chronic obstructive pulmonary disease (COPD) diagnostic questionnaires are commonly used for screening patients with COPD in primary healthcare institutions, but their accuracy is often inadequate. This study aimed to explore the accuracy of combining these two tools in screening for COPD. Methods Participants aged ≥ 40 years were recruited from primary healthcare institutions between July 2022 and July 2023. All participants completed COPD diagnostic questionnaires (CDQs) and pulmonary function tests including pre and post bronchodilator maneuvers using a portable spirometer at primary healthcare institutions and a conventional spirometer at a tertiary hospital. COPD was diagnosed based on the forced expiratory volume/forced vital capacity (FEV1/FVC) ratio measured by the conventional spirometer after administration of 400 µg of salbutamol sulfate. An FEV1/FVC ratio of < 70% indicated COPD, while an FEV1/FVC ratio of ≥ 70% was classified as non-COPD. The sensitivity and specificity of combining the portable spirometer and CDQ for COPD screening were statistically analyzed. Receiver operating characteristic (ROC) curves were employed to compare the efficacy of the portable spirometer, CDQ, and their combination in diagnosing COPD. Results Of the 2,120 participants, 264 were newly diagnosed with COPD. Among the non-COPD population, 264 participants were matched by age, sex, and BMI to form the non-COPD group. The sensitivity and specificity of the combination of the portable spirometer and CDQ in diagnosing COPD were 96.6% (95% confidence interval [CI]: 0.934–0.983) and 79.9% (95% CI: 0.745–0.845), respectively, significantly higher than those with the use of either method alone (p < 0.05). The area under the ROC curve for the combined diagnosis of COPD was 0.994 (95% CI: 0.983–0.999), with a Jordan index of 0.765. Conclusions Our findings suggest that combining the portable spirometer with the CDQ enhances COPD detection and is a valuable approach for implementation in primary healthcare institutions. Trial Registration This study has been registered in national medical research registration and filing information system of China, www.medicalresearch.org.cn , Trail registration number: MR-11-23-020214.